2020
DOI: 10.3390/app10155097
|View full text |Cite
|
Sign up to set email alerts
|

A Maturity Estimation of Bell Pepper (Capsicum annuum L.) by Artificial Vision System for Quality Control

Abstract: Sweet bell peppers are a Solanaceous fruit belonging to the Capsicum annuum L. species whose consumption is popular in world gastronomy due to its wide variety of colors (ranging green, yellow, orange, red, and purple), shapes, and sizes and the absence of spicy flavor. In addition, these fruits have a characteristic flavor and nutritional attributes that include ascorbic acid, polyphenols, and carotenoids. A quality criterion for the harvest of this fruit is maturity; this attribute is visually determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Regarding colour variations (∆E), this effect is similar to results reported by Kasim and Kasim, [31], who showed that low UV-B doses (4.46 kJ m -2 ) did not affect the colour development during 6 d at 7 • C. As observed, TSS has been related to MI and, particularly in red peppers, these two parameters have also been associated with colour development [32], which can also be contrasted with our present results. Moreover, sensory quality values can be related to the overall marketability, which has been previously reported to be increased after applying blue and red LEDs [33] or UV low doses [31,34].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding colour variations (∆E), this effect is similar to results reported by Kasim and Kasim, [31], who showed that low UV-B doses (4.46 kJ m -2 ) did not affect the colour development during 6 d at 7 • C. As observed, TSS has been related to MI and, particularly in red peppers, these two parameters have also been associated with colour development [32], which can also be contrasted with our present results. Moreover, sensory quality values can be related to the overall marketability, which has been previously reported to be increased after applying blue and red LEDs [33] or UV low doses [31,34].…”
Section: Discussionsupporting
confidence: 89%
“…‘Caro F1’ and ‘Somborka’ both form elongated, cone-shaped fruits that are quite large, and ‘Novosadka’ and ‘Berenyi F1’ form round, small fruits. All four cultivars were harvested at full size, in technological mature stage, as reported by Villaseñor et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each of the three treatments was repeated twice (two systems for one treatment) so that each contained four plants of the same cultivar. Sampling was performed when the fruits reached a sufficient size, firmness, and color (yellow) [ 15 ]. Each plant (three to four fruits from each plant) represented a separate replicate.…”
Section: Methodsmentioning
confidence: 99%
“…In order to solve the issue of writing code for a particular program to be used in the food quality inspection, fuzzy logic saves the time and effort related to the feature specification. New technologies have been established based on fuzzy logic applications in various food quality detection including sorting of orange (Jhawar, 2016), determination of moisture content in olive oil (Ortega et al, 2016), guava grading based on ripening stages (Kanade & Shaligram, 2018), and maturity estimation of bell peppers (Villaseñor-Aguilar et al, 2020). Kanade and Shaligram (2018) integrated the electronic nose sensor with fuzzy logic to classify guava according to the maturity levels.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…The findings indicated a good performance of the CNN models compared to the conventional methods such as successive projection algorithm and partial least squares. Villaseñor-Aguilar et al (2020) examined the maturity estimation of bell peppers using a fuzzy logic model. It was revealed that the fuzzy logic model obtained an accuracy of 99% in order to classify the maturity level of bell peppers.…”
Section: Applications Of Ai In Quality Determination Of Food and Agricultural Productsmentioning
confidence: 99%